Anacroneuria iporanga (Plecoptera: Perlidae): description of the nymph and biological notes - de Almeida, Lucas Henrique; Cardoso-Leite, Ricardo; Deodato, Mariana Fonte Boa; Bispo, Pitágoras Da Conceição (Zootaxa, 2019)
The Neotropical stonefly genus Anacroneuria (Perlidae) is represented by approximately 80 species in Brazil, but the nymphs of only 11 of these species have been associated and described. In this paper, we describe the previously unknown nymph of A. iporanga from Intervales State Park, São Paulo State, Brazil and present biological observations for this species